2020
DOI: 10.1002/acr.23869
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Study of Treatment Preferences for Rheumatoid Arthritis and Pharmacotherapy Acceptance: Indigenous Patient Perspectives

Abstract: Objective To explore patient preferences that influence decision‐making in the management of rheumatoid arthritis (RA) by indigenous patients living in southern Alberta, Canada. Methods We conducted a qualitative narrative‐based study within a social constructivist framework. Thirteen in‐depth interviews with indigenous patients with RA who had attended 1 of 3 rheumatology practices in southern Alberta (1 rural and 2 urban) were completed. Codes generated through 2 phases of analysis were condensed into main t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…One qualitative study conducted in this same community showed that people with arthritis commonly “tough it out” and have a hard time accepting they have a health problem [ 10 ], which could be further explained by our findings on the perception that community do not understand their experiences of pain, disability and disease. In addition, a recent qualitative study conducted in a similar population with arthritis revealed that drug-dependency stigma negatively effects on pharmacological treatment preferences [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One qualitative study conducted in this same community showed that people with arthritis commonly “tough it out” and have a hard time accepting they have a health problem [ 10 ], which could be further explained by our findings on the perception that community do not understand their experiences of pain, disability and disease. In addition, a recent qualitative study conducted in a similar population with arthritis revealed that drug-dependency stigma negatively effects on pharmacological treatment preferences [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with the E4E program lead (author LC) and team member (author RH), the Chairs of the CRA Operational Committees of Quality Care (author CB), Education (author RBK) and the Annual Scientific Meeting (author TA) undertook adaptation of the original program to create a two-phased program. While maintaining fidelity to the structure of the E4E workshops delivered to primary care physicians for diabetes care, case materials were adapted to the rheumatology specialty care context using qualitative data and patient narratives from prior research [ 5 , 16 ]. Adaptation of the materials also drew on the clinical expertise of author CB (a Métis rheumatologist providing outreach clinical care to 3 First Nations and 1 urban Indigenous clinic in southern Alberta) and author LC (a First Nations primary care physician with extensive clinical experience in urban, rural and remote Indigenous communities), as well as the curriculum development and CPD expertise of author RBK.…”
Section: Methodsmentioning
confidence: 99%
“…This may differ related to geographic considerations, such that recommendations reflecting access to care or therapy may be more important politically for advocacy purposes for populations located in rural or remote settings 13 . Indigenous populations may choose to promote questions that focus on non-Western treatment recommendations 16 , or those that examine approaches to maintain function to fulfill their social roles 10 . Different priorities for treatment recommendations could emerge too, as exemplified by elderly persons with frailty where treatment questions that prioritize symptom control and quality of life would be of greater importance than questions to support long term disease outcomes 10 .…”
Section: Priority Of the Problemmentioning
confidence: 99%
“…Further, there is stigmatization experienced by those engaged in pill-based treatment approaches related to the epidemic of opioid use disorders in the population, but also for some a preference to avoid invasive therapies. Family and community members support decision making for Indigenous patients, and trust with the healthcare provider strongly influences treatment acceptance 16 .…”
Section: Acceptability To Stakeholdersmentioning
confidence: 99%